2020
DOI: 10.1186/s12920-020-00748-3
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNAs are novel circulating biomarkers in cigarette, waterpipe smokers, E-cigarette users and dual smokers

Abstract: Background Electronic cigarettes (e-cigs) vaping, cigarette smoke, and waterpipe tobacco smoking are associated with various cardiopulmonary diseases. microRNAs are present in higher concentration in exosomes that play an important role in various physiological and pathological functions. We hypothesized that the non-coding RNAs transcript may serve as susceptibility to disease biomarkers by smoking and vaping. Methods Plasma exosomes/EVs from cigarette smokers, waterpipe smokers and dual smokers (cigarette … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 73 publications
0
30
0
1
Order By: Relevance
“…Based on our recent studies on profiling of miRNA in smokers, E-cig users, Waterpipe smokers and dual users [23], we compared the exosomal lncRNA profiles in the blood plasma from NS, CS, WP, CSWP and E-cig users. Genome-wide association studies have identified…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on our recent studies on profiling of miRNA in smokers, E-cig users, Waterpipe smokers and dual users [23], we compared the exosomal lncRNA profiles in the blood plasma from NS, CS, WP, CSWP and E-cig users. Genome-wide association studies have identified…”
Section: Discussionmentioning
confidence: 99%
“…Each subject filled a questionnaire containing information about demographics, clinical symptoms, E-cig use, and vaping history [ 25 , 26 ]. We collected 20–25 ml blood by venipuncture from smokers (CS), vapers (E-cig), waterpipe (WP) users, and subjects indulged in both cigarette smoking and waterpipe use (CSWP) as previously shown [ 23 , 26 ]. Subjects included for the study were between 18–65 yrs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations